What can we learn from experiences in general practice during the COVID-19 pandemic? A qualitative study - Corinne Rijpkema; Nanne Bos; Daan Brandenbarg; Maarten Homburg; Gina Beugel; Wietske S. Barkema; Tim olde Hartman; Jean Muris; Lilian Peters; Marjolein Berger; Robert A. Verheij; Lotte Ramerman (BMC, 2023)
Abstract Background Experiences with organizational changes in daytime general practices and out-of-hours (OOH) services during the COVID-19 pandemic may help to address the challenges in general practice care that were already a concern before the crisis. This study aimed to describe these experiences and the potential usefulness of the organizational changes for future general practice care and any future pandemics. Methods Semi-structured interviews were performed among 11 directors of OOH services, and 19 (locum) general practitioners (GPs) or practice managers, who were purposively sampled. Video or telephone interviews were performed in two rounds: between November 2020 and January 2021 and between May 2021 and August 2021. The data were analyzed using thematic analysis methods. Results Three themes emerged from the data: (1) Changes in the triage procedures; in GP practices and OOH services, stricter triage criteria were implemented, and GPs were more actively involved in the triage process. These measures helped to reduce the number of 'low urgency' face-to-face consultations. (2) Changes in GP care; there was a shift towards video and telephone consultations, allowing GPs to spend more time with patients during the remaining face-to-face consultations. For chronic patients, the shift towards telemonitoring appeared to encourage self-care, and postponing face-to-face consultations for regular checkups appeared to be unproblematic for stable patients. (3) Coordination of GP care and information communication flow during the COVID-19 pandemic; OOH directors perceived a lack of consistency in the information from various governmental and non-governmental parties on containment measures and guidelines related to COVID-19, making it difficult to act on them. The COVID-19 pandemic intensified collaboration between GPs, OOH services, and other healthcare professionals. Conclusions The results of this study indicate that some of the organizational changes, such as stricter triage, remote consultations, and changes in managed care of chronic patients, may help in tackling the pre-existing challenges in GP care from before the COVID-19 pandemic. However, more extensive research and continuous monitoring are necessary to establish the effects on patients and their health outcomes. To navigate future pandemics, the intensified collaboration between health professionals should be maintained, while there is considerable room for improvement in the provision of unambiguous information.